An optimal load shedding approach for transmission networks using Particle Swarm Optimization (PSO) technique / Mohd Farid Mohd Rawi - Mohd Rawi, Mohd Farid (2009)
This thesis presents an optimal load shedding approach for transmission networks using Particle Swarm Optimization (PSO). The study involves the development of PSO algorithm and engine to address load shedding in loss minimization. Electrical power transmission network typically connects power plants to multiple substations near a populated area. Electrical power transmission system interconnects generators and loads and generally provides multiple paths among them. Load shedding is one of the challenging problems in deregulated power systems. By employing the PSO, it is estimated to maintain the system, to minimize the sum of curtailed load and also to minimize the system losses. The proposed method is tested on transmission network IEEE 30-bus system for more practical applications.